2021
DOI: 10.1093/hmg/ddab304
|View full text |Cite
|
Sign up to set email alerts
|

C/D box snoRNA SNORD113-6/AF357425 plays a dual role in integrin signalling and arterial fibroblast function via pre-mRNA processing and 2′O-ribose methylation

Abstract: We have previously shown that C/D box snoRNAs transcribed from the DLK1-DIO3 locus on human chromosome 14 (14q32) are associated with cardiovascular disease. DLK1-DIO3 snoRNAs are ‘orphan snoRNAs’ that have no known targets. We aimed to identify RNA targets and elucidate the mechanism-of-action of human SNORD113–6 (AF357425 in mice). As AF357425-knockout cells were non-viable, we induced overexpression or inhibition of AF357425 in primary murine fibroblasts and performed RNA-Seq. We identified several pre-mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…We investigated whether AF357425/SNORD113-6 could also target small RNAs besides the previously identified integrin signaling mRNA targets. 33 We found that tRNAs are the predominant small RNA target of AF357425 in primary fibroblasts. Inhibition of AF357425/ SNORD113-6 led to an overall decrease in tRFs, and, compared with overexpression of the snoRNA, less larger (>30 nucleotides) and more smaller (<30 nucleotides) tRFs were formed.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We investigated whether AF357425/SNORD113-6 could also target small RNAs besides the previously identified integrin signaling mRNA targets. 33 We found that tRNAs are the predominant small RNA target of AF357425 in primary fibroblasts. Inhibition of AF357425/ SNORD113-6 led to an overall decrease in tRFs, and, compared with overexpression of the snoRNA, less larger (>30 nucleotides) and more smaller (<30 nucleotides) tRFs were formed.…”
Section: Discussionmentioning
confidence: 74%
“…11 Indeed, knockdown of SNORD113-6 altered human arterial fibroblast function. 12 C/D box snoRNAs associate with four conserved ribonucleoproteins NHP2L1, NOP56, NOP58, and Fibrillarin (FBL). FBL is the methyltransferase that catalyzes 2 0 Ome.…”
Section: Introductionmentioning
confidence: 99%
“… 7 They also reported a role for AF357425/SNORD113, focusing on its mRNA targeting capacity resulting in regulation of the integrin signaling pathway. 8 This new report expands the knowledge considerably, showing that AF357425/SNORD113-6 targets tRNAs, protecting the tRNA from cleavage into small fragments. Specifically, they demonstrated that AF357425/SNORD113-6 induces 2-O-methylation (2′Ome) of the mature tRNALeu(TAA), thereby protecting against site-specific tRNA fragmentation.…”
mentioning
confidence: 74%
“…They also reported direct impairment of translation by the methylation of the Pxdn coding sequence. Recently, van Ingen et al found that the orphan snoRNA snord113-6 is required for fibroblast cell survival and methylates multiple mRNAs within the integrin pathway; inhibition of this snoRNA reduced mRNA methylation and increased degradation of the targeted mRNAs, with mixed effects on subsequent protein expression (van Ingen et al, 2022). Furthermore, several studies have reported widespread 2’-O-methylation of eukaryotic mRNAs (Dai et al, 2017; Hsu et al, 2019), although the origin and function of these methylation sites is largely unknown.…”
Section: Discussionmentioning
confidence: 99%